PENGEMBANGAN MODEL KESIAPAN KNOWLEDGE MANAGEMENT UNTUK PERGURUAN TINGGI SWASTA - Faradillah Faradillah (UNIVERSITAS INDO GLOBAL MANDIRI)
Private colleges as a form of business engaged in the education course are expected to have good management to knowledge. How knowledge is captured, documented, processed, shared and reused as a knowledge management process is a key business process at a private college. Surely a company can survive and thrive when the business processes running smoothly. It is the basis of this paper was compiled. By identifying the factors that influence the adoption of knowledge management in organizations, this paper tries to develop these factors into an indicator Builder knowledge management framework for private colleges through a literature review. The knowledge management framework is expected to be used as a reference that helps private-college readiness as a strategy the application of knowledge management in the company as one of the effort to avoid the failure of adoption. Key words:Knowledege management, private framework, KM